The atmospheric quasi-biweekly oscillation during the Jiangnan Meiyu onset period - Sun, Tianle; Yao, Suxiang; Huang, Qian (Frontiers in Earth Science, 2022)
Meiyu is a typical rainy season during the East Asian Summer Monsoon whose early or late onset is closely related to an abnormal amount of rainfall. Based on ERA-interim daily reanalysis data from 1979 to 2019 and the Meiyu index dataset provided by the CMA (China Meteorological Administration), the characteristics of the intraseasonal oscillation (ISO) in different latitudes during the Jiangnan Meiyu onset period were examined. During the Meiyu onset period, the analysis of 500 hPa geopotential height shows that the key regions of circulation anomaly include the Ural Mountains in mid-high latitudes and the Northwest Pacific in low latitudes. Moreover, the geopotential height anomaly of the two regions shows significant quasi-biweekly scale (10-30 days) characteristics. The diagnosis of quasi-biweekly geopotential tendency shows that the height variation in the mid-high latitude key region mainly depends on the influence of temperature advection, while the variation in the low-latitude key region relies on vorticity advection. Over the mid-high latitudes, the height anomaly of the Ural Mountains gradually increases before the day of Meiyu onset, and the contribution of quasi-biweekly oscillation (QBWO) to the total anomaly is approximately 55.9%. The fluctuations from Europe and the Aleutians spread toward the key region, and the abnormal warm advection lies over the key region, contributing to the formation of the Ural-blocking pattern. Meanwhile, in the key region located over the Western Pacific, the contribution of the quasi-biweekly component reaches 51.2%. The oscillations over the Western Pacific propagate southwestward along the East Asian coast, while fluctuations over the East Asian continent migrate southward. Throughout this period, the negative vorticity advection occupies the key region, which is conducive to both the positive geopotential height variation and the maintenance of the Western Pacific Subtropical High. Thus, the migration of the QBWO in different latitudes could be an extended-range signal of the Jiangnan Meiyu prediction.